A Systematic Review of Randomized Controlled Trials Comparing Hypertonic Sodium Solutions and Mannitol for Traumatic Brain Injury: Implications for Emergency Department Management. (April 2016) - Burgess, Sarah; Abu-Laban, Riyad B.; Slavik, Richard S.; Vu, Erik N.; Zed, Peter J.
Objective: To comparatively evaluate hypertonic sodium (HTS) and mannitol in patients following acute traumatic brain injury (TBI) on the outcomes of all-cause mortality, neurological disability, intracranial pressure (ICP) change from baseline, ICP treatment failure, and serious adverse events.Data Sources: PubMed, EMBASE, CENTRAL, Cochrane Database of Systematic Reviews, ClinicalTrials.gov, and WHO ICTRP (World Health Organization International Clinical Trials Registry Platform) were searched (inception to November 2015) using hypertonic saline solutions, sodium chloride, mannitol, osmotic diuretic, traumatic brain injury, brain injuries, and head injury . Searches were limited to humans. Clinical practice guidelines and bibliographies were reviewed.Study Selection and Data Extraction: Prospective, randomized trials comparing HTS and mannitol in adults (≥16 years) with severe TBI (Glasgow Coma Scale score ≤8) and elevated ICP were included. ICP elevation, ICP reduction, and treatment failure were defined using study definitions.Data Synthesis: Of 326 articles screened, 7 trials enrolling a total of 191 patients met inclusion criteria. Studies were underpowered to detect a significant difference in mortality or neurological outcomes. Due to significant heterogeneity and differences in reporting ICP change from baseline, this outcome was not meta-analyzed. No difference between HTS and mannitol was observed for mean ICP reduction; however, risk of ICP treatment failure favored HTS (risk ratio [RR] = 0.39; 95% CI = 0.18-0.81). Serious adverse events were not reported.Conclusions: Based on limited data, clinically important differences in mortality, neurological outcomes, and ICP reduction were not observed between HTS or mannitol in the management of severe TBI. HTS appears to lead to fewer ICP treatment failures.